Seizure and epilepsy care the pocket epileptologist - Landazuri, Patrick ca. 20./21. Jh; Lecumberri, Nuria Lacuey ca. 20./21. Jh; Bertran, Laura Vilella ca. 20./21. Jh; Farrenburg, Mark ca. 20./21. Jh; Lhatoo, Samden ca. 20./21. Jh (Cambridge medicine, 2023)
Epilepsy is a frequently encountered disease, affecting 1-2% of the population, but one that is often mistreated due to misunderstandings of specific diagnoses and treatments. This practical manual provides a succinct and clinically relevant reference of routine clinical epilepsy care. The book is designed around the four main aspects of an epilepsy patient's care: first seizure, inpatient epilepsy care, outpatient epilepsy care, and diagnostic modalities. These four aspects are carefully delineated to illustrate the key differences in best practice management. Rational use of EEG and imaging testing is thoroughly covered to guide improved utility of these results. Caring for the mental health of epilepsy patients is also covered, as this is pertinent at every stage and location of epilepsy patient care. An excellent resource for neurology trainees at the resident, fellow, and medical student level as well as advanced practice providers